2015
DOI: 10.1115/1.4029608
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Vegetation on Turbulence Characteristics and Reynolds Shear Stress in Partly Vegetated Channel

Abstract: From the perspective of vegetation density, this research studies the influence of vegetation on turbulence characteristics and Reynolds shear stress in partly vegetated channel via a series of experiments. Natural reed is employed to simulate the emergent vegetation in rivers. Different vegetation densities including vegetated and unvegetated cases are considered in the research. The results of the research demonstrate that emergent vegetation may force the water flowing from vegetated areas to unvegetated ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The turbulence intensities pattern in both vegetated and non-vegetated channels represent declines in directions of the flow. Study by Zhang et al [22] also resulted in the same manner as for vegetated unvarying bedforms.…”
Section: Resultsmentioning
confidence: 85%
“…The turbulence intensities pattern in both vegetated and non-vegetated channels represent declines in directions of the flow. Study by Zhang et al [22] also resulted in the same manner as for vegetated unvarying bedforms.…”
Section: Resultsmentioning
confidence: 85%
“…As demonstrated by previous studies, vegetation density alters the characteristic length and time scales of energetic motion in open channel, the standard boundary-layer flows could also be shifted to canopy flows gradually with increasing vegetation density (Poggi et al, 2004), In fact, higher vegetation densities are generally used in the practices of river restorations to produce better ecological and environmental benefits (Nikora et al, 2013). Based on the comprehensive considerations on previous study (Velasco et al, 2003, Zhang et al, 2015a, field investigations and the reality of punched plates, a relatively dense vegetation density of 202 stems/m 2 is used in the present research.…”
Section: Methodsmentioning
confidence: 86%
“…For the purposes of ecological restoration and pollutant reduction, aquatic vegetation planting and management with different configurations have become common approaches in recent years (Zhou et al, 2006;Callow, 2012;Lama et al, 2021). For the rigid vegetation, due to the additional vegetal retardance, it has been noticed that vegetation planted in rivers may raise the water depth and reduce flow velocity, and therefore increase the potential risk of flooding or sediment silting (Zhang et al, 2015a;Friberg et al, 2017). However, the complexity of the combinations of hydraulic and vegetation conditions hindered the development the determination of the alternations of flow state due to vegetation block (Stone and Shen, 2002;Yagci et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Anisotropy analysis showed that a one-dimensional turbulence is dominant in a partly vegetated channel. Zhang et al [26] studied the effect of vegetation density on flow turbulence characteristics and Reynolds shear stress in a partly vegetated channel. A series of experiments were carried out in a rectangular channel of 30 m length (facilitates the generation of gradual varied flow), 1.3 m width, and 0.8 m depth.…”
Section: Introductionmentioning
confidence: 99%